Pemberdayaan Komunitas UMKM Makmur Bersama Untuk Meningkatkan Kualitas dan Legalitas Digitalisasi Ekonomi Masyarakat Kelurahan Karangbesuki - Mohamad Rodhi Faiz; Sujito, Sujito; Triyanna Widiyaningtyas; Budi Wibowotomo; Rajib Muhammad Basthomy (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Along with the development of the economic sector and the rapid pace of the information sector, the position of MSMEs in market competition schemes is often left behind by businesses with larger capital. With more modern marketing methods and legal activities that more clearly affect the relationship of trust between sellers and consumers. So Empowerment and Training is needed on how to build a business that has legality and quality so that it can survive in business competition and can develop into a more modern one. This time the community service raised this problem and collaborated with Makmur Bersama MSME Community partners. Partners are located in Karangbesuki Village, Sukun District, Malang City, around the Malang State University Campus. This community service proposes a program of empowerment and assistance in obtaining business licensing starting from Business Identification Numbers (NIB), Home Industry Product Numbers (P-IRT), and Product Halal Certification.